2017
DOI: 10.4314/tjpr.v16i8.26
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant <i>Staphylococcus aureus</i> isolates from Iranian restaurant food samples: Panton-Valentine Leukocidin, SCCmec phenotypes and antimicrobial resistance

Abstract: (92.77 %), oxacillin (83.13 %) and azithromycin (71.08 %). All MRSA bacteria were resistant to at least 2 antibiotics (100 %). TetK (80.72 %), linA (67.46 %), aadA1 (62.65 %), and msrA (55.42 %) were the most frequently identified resistance genes. SCCmec V (57.83 %), SCCmec Iva (55.42 %) and SCCmec IVb (30.12 %)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
4
3
0
Order By: Relevance
“…Most of them reported the con rmation of phenotypic pattern of antibiotic resistance by the presence of diverse antibiotic encoding genes [16,66,76,77] High distribution of blaZ, mecA, tetK, aacA-D, msrA, ermA, gyrA, dfrA1, and blaCTX-M antibiotic resistance encoding genes in the S. aureus bacteria isolated from diverse kinds of food samples and also human clinical infections have been reported from Iran [66,76,78], India [79], Georgia [72], Nigeria [80], Germany [81], Egypt [82], and Switzerland [83]. Comparable to our research, higher prevalence of msrA than msrB [66,76,78,84], ermA than ermB [66,76,78,84,85], tetK than tetM [66,76,78,84] vatA than vatB [66,76,78,84], vanA than vanB [66,76,78,84,85] and gyrA than grlA [66,76,84] antibiotic resistance encoding genes has been reported in recent years. Our ndings were also disclosed a higher prevalence of phenotypic pro le of resistance than genotypic pro le.…”
Section: Discussionsupporting
confidence: 76%
“…Most of them reported the con rmation of phenotypic pattern of antibiotic resistance by the presence of diverse antibiotic encoding genes [16,66,76,77] High distribution of blaZ, mecA, tetK, aacA-D, msrA, ermA, gyrA, dfrA1, and blaCTX-M antibiotic resistance encoding genes in the S. aureus bacteria isolated from diverse kinds of food samples and also human clinical infections have been reported from Iran [66,76,78], India [79], Georgia [72], Nigeria [80], Germany [81], Egypt [82], and Switzerland [83]. Comparable to our research, higher prevalence of msrA than msrB [66,76,78,84], ermA than ermB [66,76,78,84,85], tetK than tetM [66,76,78,84] vatA than vatB [66,76,78,84], vanA than vanB [66,76,78,84,85] and gyrA than grlA [66,76,84] antibiotic resistance encoding genes has been reported in recent years. Our ndings were also disclosed a higher prevalence of phenotypic pro le of resistance than genotypic pro le.…”
Section: Discussionsupporting
confidence: 76%
“…Our ndings addressed the higher distribution of tetK (80.55%) than tetM (66.66%) antibiotic resistance genes. Similarly, higher incidence of tetK than tetM antibiotic resistance genes was also reported previously [5,6,8,10,40,46,50,51]. Higher incidence of antibiotic resistance genes reported in some previously published papers is due to the fact that they examined the distribution of antibiotic resistance genes amongst the methicillin-resistant S. aureus (MRSA) strains.…”
Section: Discussionsupporting
confidence: 68%
“…These genes are mainly encoded resistance against quinupristindalfopristin and streptogramin antibiotic agents. R Ranjbar, MHS Shahreza, E Rahimi and N Jonaidi-Jafari [50]reported that the total incidence of vatA, vatB and vatC antibiotic resistance genes amongst the S. aureus strains isolated from foods with animal origins were 38.55%, 19.27% and 9.63%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies on S. aureus isolation from street vended foods from India and the studies carried out in Silchar city, Assam by Sharma and Mazumdar (2014) revealed that 14.2% street vended food samples were positive for S. aureus while in Gangtok and Nainital, it was detected in 19.5% and 33% street vended food samples (Kharel et al 2016). Various workers reported that between 2.42% and 69.74% restaurant/street food samples harbored MRSA (Rhee and Woo 2010;Rizek et al 2011;Ranjbar et al 2017), thus responsible for health implications to the consumer. In another study, enterotoxigenic S. aureus was detected in 91 (60%) samples of coriander sauce, 87 (58%) samples of coconut slices and 129 (86%) samples of readyto-eat salads in New Delhi and Patiala City (Ghosh et al 2007).…”
Section: Resultsmentioning
confidence: 99%